Sex and gender differences in T cells in hypertension - Tipton, Ashlee J. (Clin Ther, 2014)
PURPOSE: Hypertension is a major risk factor for the development of cardiovascular disease, stroke and end-organ damage. There is a sex difference in blood pressure (BP) that begins in adolescence and continues into adulthood, where men have a higher prevalence of hypertension compared to women until the sixth decade of life. Less than 50% of hypertensive adults in the United States taking medication manage to control their BP to recommended levels using current therapeutic options, and women are more likely than men to have uncontrolled high BP. This is despite the fact that more women compared to men are aware that they have hypertension and women are more likely to seek treatment for the disease. Novel therapeutic targets need to be identified in both sexes to increase the percentage of hypertensive individuals with controlled BP. The purpose of this article is to review the available literature on the role of T cells in BP control in both sexes, and the potential therapeutic application/implications of targeting immune cells in hypertension. METHODS: A search of PUBMED was conducted to determine the impact of sex and gender on T cell-mediated control of BP. The search terms included sex, gender, estrogen, testosterone, inflammation, T cells, T regulatory cells, Th17 cells, hypertension and blood pressure. Additional data were included from our laboratory examining cytokine expression in the kidney of male and female SHR and differential genes expression in both the renal cortex and mesenteric arterial bed of male and female SHR. FINDINGS: There is a growing basic science literature regarding the role of T cells in the pathogenesis of hypertension and BP control, however, the majority of this literature has been performed exclusively in males despite the fact that both men and women develop hypertension. There is increasing evidence that while T cells also mediate BP in females, there are distinct differences in both the T cell profile and the functional impact of “male” vs. “female” T cells on cardiovascular health, although more work is needed to better define the relative impact of different T cell subtypes on BP in both sexes. IMPLICATIONS: The challenge now is to fully understand the molecular mechanisms by which the immune system regulates BP and how the different components of the immune system interact so that specific mechanisms can be targeted therapeutically without compromising natural immune defenses.